ANALISIS KUALITATIF STRATEGI PENETAPAN KUPON SBR OLEH DJPPR TERHADAP PERUBAHAN BI7DRR PERIODE 2021–2024 - Aulia Nissa Ahnafia; Yusnita Sarnanda; Az Zahra Keila Adjani; Raihan Maulana; Muhammad Yogi Hermanto; Muhammad Diva Nurliyanto (CV. Denasya Smart Publisher, 2025)
This study aims to qualitatively analyze the coupon-setting strategy employed by the Directorate General of Budget Financing and Risk Management (DJPPR) in response to fluctuations in Bank Indonesia's benchmark interest rate, specifically the BI 7-Day Reverse Repo Rate (BI7DRR), during the 2021–2024 period. Using a descriptive-analytical approach based on a literature review, the research examines official policy documents, historical BI7DRR data, and relevant academic studies. The findings indicate that DJPPR implemented a floating with floor coupon mechanism as an adaptive strategy to address interest rate volatility. This mechanism has proven effective in maintaining the appeal of Savings Bond Ritel (SBR) among retail investors, while also reflecting the synergy between fiscal and monetary policy in managing national debt instruments